Factors Related to Cost and Quality of Life of Makhueajae Primary Health Care Center Outpatients - Sakarinkhul, Pokin (Journal of Health Science of Thailand, 2017)
Due to patient distribution policy, primary care unit cost was increasing resulting from the increase of outpatient visits. Cost and utility of caring should be evaluated. Direct medical cost (CDM) and direct non-medical cost (CDNM) were collected from Makhueajae Primary Health Care Center (PHCC in Muang, Lamphun) records and 378 patients from 21 villages who visited PHCC OPD during Octoer 2009 - April 2010 were randomly selected by stratified random sampling and were also interviewed for further information. The results showed the total cost of 1,109.22 baht/patient (CDM = 847.54 baht/ patient, CDNM = 261.68 baht/patient) related to quality of life score (p<0.01) evaluated by EQ-5D (mean = 0.75). Also, female, age more than 60 years, having chronic disease(s), and poverty were related to utility scores (p<0.01).